2020
DOI: 10.1021/acs.chemrev.0c00718
|View full text |Cite
|
Sign up to set email alerts
|

Jahn–Teller and Pseudo-Jahn–Teller Effects: From Particular Features to General Tools in Exploring Molecular and Solid State Properties

Abstract: Fe atom results in their nonzero overlap producing a covalence contribution to this bonding. Reprinted with permission from ref 5. Copyright (2006) I. B. Bersuker. Chemical Reviews pubs.acs.org/CR Review

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 209 publications
3
100
0
5
Order By: Relevance
“…Indeed, "in quantum-mechanical description of the motions of the electrons and nuclei, the notion of space configuration is introduced in the adiabatic approximation, in which it is assumed that due to the huge difference between the masses of electrons and nuclei, the fast moving electrons follow adiabatically the much slower nuclear motions. Here adiabatic means that at each instantly fixed nuclear configuration, a stationary electronic charge distribution is achieved, The system in a stable nondegenerate electronic state has a relatively low-lying (at the energy gap ∆ 0 ) double-degenerate excited state with a strong JTE-induced distortion, its stabilization energy E JT being larger than ∆ 0 , thus producing a more stable ground state distorted along Q; this is the hidden-JTE; (b) In a system with a similar nondegenerate ground state as in (a), the excited state is nondegenerate, too, but there is a near-neighbor next excited state (with a relatively small energy gap between them ∆ 12 ), which allows for their PJT coupling with E PJT > ∆ 0 , resulting in a distorted ground state, similar to the case (a); this is the hidden-PJTE [9,14,15].…”
Section: Improved (Quantum) Definition Of Stereo-chemical Space Configuration Of Polyatomic Systems With Regard To Symmetrymentioning
confidence: 88%
See 3 more Smart Citations
“…Indeed, "in quantum-mechanical description of the motions of the electrons and nuclei, the notion of space configuration is introduced in the adiabatic approximation, in which it is assumed that due to the huge difference between the masses of electrons and nuclei, the fast moving electrons follow adiabatically the much slower nuclear motions. Here adiabatic means that at each instantly fixed nuclear configuration, a stationary electronic charge distribution is achieved, The system in a stable nondegenerate electronic state has a relatively low-lying (at the energy gap ∆ 0 ) double-degenerate excited state with a strong JTE-induced distortion, its stabilization energy E JT being larger than ∆ 0 , thus producing a more stable ground state distorted along Q; this is the hidden-JTE; (b) In a system with a similar nondegenerate ground state as in (a), the excited state is nondegenerate, too, but there is a near-neighbor next excited state (with a relatively small energy gap between them ∆ 12 ), which allows for their PJT coupling with E PJT > ∆ 0 , resulting in a distorted ground state, similar to the case (a); this is the hidden-PJTE [9,14,15].…”
Section: Improved (Quantum) Definition Of Stereo-chemical Space Configuration Of Polyatomic Systems With Regard To Symmetrymentioning
confidence: 88%
“…This is the pseudo JTE (PJTE) (see in refs. [7][8][9]13]). More recently, it was also shown that there may be "hidden" JTE and "hidden" PJTE when the state under consideration is neither degenerate, nor pseudodegenerate, but there is a strong JTE or PJTE in the excited state that penetrates the ground state [14,15].…”
Section: Origin Of Spontaneous Symmetry Breaking In Atomic Matter: the Jahn-teller Effect (Jte) Pseudo-jte (Pjte) Hidden-jte And Hidden-pmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Their consequences, termed JT and pJT effects, are commonly seen in spectroscopy, structural chemistry, solid-state physics, and optoelectronics. [7][8][9][10][11][12][13][14][15][16][17][18] The JT and pJT interactions belong to the broader category of vibronic interactions, since they involve interactions between electronic and vibrational degrees of freedom. 3,19 Naturally, accurate vibronic Hamiltonians for JT/pJT problems are of critical importance to simulate and understand the associated JT/pJT effects.…”
Section: Introductionmentioning
confidence: 99%